2014
DOI: 10.5539/gjhs.v7n1p228
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Lifestyle in Women With Polycystic Ovary Syndrome and Healthy Women

Abstract: Given the high prevalence of polycystic ovary syndrome (PCOS), and that a lifestyle is recognized effective in development of many diseases, this study aimed to compare lifestyle of women with PCOS and healthy women. Nor are there sufficient studies on the difference between lifestyle of these people with that of healthy people. Furthermore, studies show that changes in lifestyle improve this disease. This descriptive-comparative study was conducted on 65 women with PCOS and 65 healthy women of 18 to 45 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 20 publications
2
34
0
5
Order By: Relevance
“…However, this important information about obesity and its association with increasing levels of free testosterone was only known to 56.3% of the participants. It is one of the important information associated with the disease, as this association can aggravate the clinical presentation of the disease in the form of clinical hyperandrogenism and anovulation (Sedighi et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this important information about obesity and its association with increasing levels of free testosterone was only known to 56.3% of the participants. It is one of the important information associated with the disease, as this association can aggravate the clinical presentation of the disease in the form of clinical hyperandrogenism and anovulation (Sedighi et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…A weight loss of 5% to 10% can have significant clinical impacts on psychological, reproductive and metabolic features of the disease (H. Teede et al, 2010). Exercise can help to improve the condition of women diagnosed with PCOS in two ways: firstly in reducing insulin resistance and secondly by decreasing body fat, which is the storage medium for estrogen and steroid hormones (Sedighi et al, 2014). The knowledge of life style modification with diet and exercise as a self-management approach to decrease weight and to minimize the complications was known to most of the participants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study conducted by Sedighi S et al it was observed that there was a significant association between PCOS and low physical activity. 18 The OGTT test of the present study revealed that about 41% of the study patients with PCOS had deranged oral glucose tolerance. Similar results were found in a study conducted by Coles N et al which showed that 16% of the patients had impaired glucose tolerance.…”
Section: Discussionmentioning
confidence: 45%
“…PCOS would also stimulate depression and reduce the quality of life as women may indulge in unhealthy diets, have cravings for high GI diets and fall short in exercise (8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%